Pengaruh Kegiatan Pariwisata Rammang-Rammang terhadap Peningkatan Ekonomi Masyarakat - Mutya Alizia Putri. B; Rudi Latief; Ilham Yahya (Journal of Urban Planning Studies, 2020)
Mutya Alizia Putri. B, 2020 "The Effect of Rammang-Rammang Tourism Activities on the Economic Improvement of the Maros Regency Community". Supervised by Rudi Latief and Ilham Yahya. The purpose of this study was to identification the relationship between Rammang-Rammang tourism activities and the economic improvement of the local community in Maros Regency. As well as to identification efforts to improve the community's economy related to Rammang-Rammang tourism activities in Maros Regency. For the Maros Regency Government, this research can used as a reference for the considerate of policy formulation in the tourism sector related to improving the local economy by taking into account the perceptions and preferences of the community so that policies implemented can implemented optimally. The variables used are the age of tourism and tourism income. The analytical method used is in the form of correlation analysis (r), than compiling efforts to improve the community's economy related to Rammang-Rammang tourism activities in Maros Regency with descriptive analysis methods. All variables have an effect on improving the community's economy in the tourism area of ​​Rammang-Rammang, Maros Regency. So that efforts that can used in improving the economy of the tourism area community are by improving tourism facilities and infrastructure as stated in the Maros Regency Regulation No. 4 of 2012 about RTRW. Keywords: Tourism, Influence, Community Economy, Income.